Very Late Development of Coronary Artery Aneurysm with Total Occlusion following Sirolimus-Eluting Stent Implantation - Mukku, Venkata K.; Cai, Qiangjun; Barbagelata, Alejandro; Conti, Vincent R.; Fujise, Ken (International Journal of Angiology, 2012)
A 41-year-old African American woman presented with chest pain and was found to have non-ST segment elevation myocardial infarction with a peak cardiac troponin I of 28.5. Elective cardiac catheterization revealed a 70% ostial left anterior descending (LAD) artery stenosis. The patient underwent percutaneous coronary intervention and a sirolimus-eluting stent (Cypher, Miami, FL, 3.5 × 8 mm) was successfully deployed. Three years after stent implantation, the patient presented with recurrent angina. Repeat coronary angiography revealed a large aneurysm involving the proximal portion of the stent with a total occlusion at the mid to distal portion of the stent with collaterals to LAD from left circumflex artery. The patient underwent coronary artery bypass surgery with left internal mammary artery graft to LAD and ligation of LAD at its origin proximal to the aneurysm.
Keywords: coronary artery aneurysm; coronary artery bypass; sirolimus-eluting stent; percutaneous coronary intervention